Coal, power, and Kyoto protocol: regulating greenhouse gas emissions in Poland and Kazakhstan - Zhekey, Ainur (Nazarbayev University School of Sciences and Humanities, 2016)
This thesis focuses on coal-using power generation companies’ behavior under state policies and the outcomes of greenhouse gas emissions reduction efforts (as a result of the Kyoto Protocol and COP 21) of two countries, Poland and Kazakhstan. Why did these countries differ in the reduction of greenhouse gas emissions levels as both have followed the same Kyoto Protocol’s obligations and both have similar coal production and consumption rates? Addressing this empirical question helps investigate broader theoretical questions of how and why some countries take implementation of international regimes seriously while others do not. Is the difference due to faulty international agreement or due to domestic politics, which shape the implementation of, or failure to implement, international environmental obligations? To understand this difference deeper I used two embedded case studies, analyzed government documents and company GRI reports, data from International Energy Statistics (EIA), ‘United Nations Framework on Climate Change’ (UNFCCC), ‘Intergovernmental Panel on Climate Change’ (IPCC), and environmental policies for sustainable development, and conducted interviews with 10 employees and managers from a coal-powered generation company in Kazakhstan. On the basis of my evidence, I have reached the following three conclusions. First, domestic political constraints as defined by financial, informational, and personnel constraints in Kazakhstan were stronger than in Poland, and Kyoto’s approach to tackle the emissions issue was not effective. Second, European Union (EU) membership helped Poland to reduce its emissions as it both pressured Poland to implement environmental obligations and helped reduce domestic political constraints. Third, the difference between the political regimes of two nations (Poland being a “flawed democracy”; and Kazakhstan being an “autocracy”) was not sufficient to explain for why international agreements work for Poland and do not work for Kazakhstan. Many scholarly works exist that examine environmental impact reduction in Poland and its performance under the international climate change agreements; however, there is a void in the existing literature for Kazakhstan due to its comparatively slow reform process.
Keywords: greenhouse gas; coal-using power; Kyoto protocol